2008
DOI: 10.1111/j.1553-2712.2008.00267.x
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Department Crowding and Decreased Quality of Pain Care

Abstract: Objectives: The objective of this study was to evaluate the association of emergency department (ED) crowding factors with the quality of pain care.Methods: This was a retrospective observational study of all adult patients ( ‡18 years) with conditions warranting pain care seen at an academic, urban, tertiary care ED from July 1 to July 31, 2005, and December 1 to December 31, 2005. Patients were included if they presented with a chief complaint of pain and a final ED diagnosis of a painful condition. Predicto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
92
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(97 citation statements)
references
References 38 publications
4
92
0
1
Order By: Relevance
“…Prolonged ED LOS can lead to delays in diagnosis and/or treatment for specific conditions, such as timely administration of antibiotics for pneumonia 1,34 and febrile neonates, 35 reperfusion for acute myocardial infarction patients, 2,34 orders and completion of computed tomography scans for stroke, 36 medication orders for asthma, 37 and administration of analgesics for hip fracture and other painful conditions. 3,4,38,39 Crowding in the ED may also affect disposition decisions and has been associated with a lower likelihood of hospital admission in a study of pediatric ED patients with asthma or gastroenteritis. 40 The current study adds to this prior work by demonstrating an association with serious adverse events when ED crowding is expressed as shift-level performance on Ontario's ED LOS benchmarks.…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged ED LOS can lead to delays in diagnosis and/or treatment for specific conditions, such as timely administration of antibiotics for pneumonia 1,34 and febrile neonates, 35 reperfusion for acute myocardial infarction patients, 2,34 orders and completion of computed tomography scans for stroke, 36 medication orders for asthma, 37 and administration of analgesics for hip fracture and other painful conditions. 3,4,38,39 Crowding in the ED may also affect disposition decisions and has been associated with a lower likelihood of hospital admission in a study of pediatric ED patients with asthma or gastroenteritis. 40 The current study adds to this prior work by demonstrating an association with serious adverse events when ED crowding is expressed as shift-level performance on Ontario's ED LOS benchmarks.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have studied the social context of the ED environment and the potential effect on the management of pain with a recent emphasis on effect of ED overcrowding (Bernstein et al, 2009;Duignan & Dunn, 2009;Hwang, Richardson, Sonuyi, & Morrison, 2006;Hwang et al, 2008;Pines, Shofer, Isserman, Abbuhl, & Mills, 2010;Russo, 2010;Tanabe, 1996;Tanabe & Buschmann, 1999). Of those studies located, three quantitative studies measured ED nurses' perceived barriers to general pain management (Duignan & Dunn, 2009;Tanabe, 1996;Tanabe & Buschmann, 1999), four studies examined the effect of ED crowding on quality of pain care, analgesia in patients with back pain, the management of pain in older adults with hip fracture, and patients who presented at triage with severe pain (Hwang et al, 2006;Hwang et al, 2008;Pines & Hollander, 2008;Pines et al, 2010).…”
Section: Environmental Issues and Policies In The Edmentioning
confidence: 99%
“…Of those studies located, three quantitative studies measured ED nurses' perceived barriers to general pain management (Duignan & Dunn, 2009;Tanabe, 1996;Tanabe & Buschmann, 1999), four studies examined the effect of ED crowding on quality of pain care, analgesia in patients with back pain, the management of pain in older adults with hip fracture, and patients who presented at triage with severe pain (Hwang et al, 2006;Hwang et al, 2008;Pines & Hollander, 2008;Pines et al, 2010). One qualitative study was located that identified the theme things that hinder decision-making for pediatric pain (Russo, 2010).…”
Section: Environmental Issues and Policies In The Edmentioning
confidence: 99%
“…They are also medical homes for many uninsured people and have been shown to reduce non-emergent visits to emergency departments [24][25][26]. While free clinics were likely never considered as the ACA was drafted, this act has already begun to impact their plans; therefore, states should anticipate meaningful and unanticipated consequences to the safety-net system for the uninsured population as a whole.…”
mentioning
confidence: 99%